Some Shetland brochs and standing stones: (Being the Chalmers-Jervise Prize Essay for the year 1911) - Stout, Elizabeth (Proceedings of the Society of Antiquaries of Scotland, 1912)
Standing stones, or the remains of them, are to be found in almost every parish. The majority are roughly fashioned into a sort of slab, although some of them exhibit no distinct formation of this kind. Their number is uncertain and they occur on hills and in valleys. Descriptions and sketches of a number of individual stones are provided along with some local traditions linked to them. There are approximately eighty brochs in Shetland, a small number of which have been excavated. The morphological characteristics of a selection of brochs are described and illustrated.